2015
DOI: 10.1264/jsme2.me15041
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Skin Microbiota in Italian Stream Frogs (<i>Rana italica</i>) Infected and Uninfected by a Cutaneous Parasitic Disease

Abstract: In human and wildlife populations, the natural microbiota plays an important role in health maintenance and the prevention of emerging infectious diseases. In amphibians, infectious diseases have been closely associated with population decline and extinction worldwide. Skin symbiont communities have been suggested as one of the factors driving the different susceptibilities of amphibians to diseases. The activity of the skin microbiota of amphibians against fungal pathogens, such as Batrachochytrium dendrobati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 55 publications
(120 reference statements)
2
27
1
Order By: Relevance
“…dendrobatidis bacteria likely have general antimicrobial properties (52) and may provide a general defensive benefit against pathogens to the host (9,13,23,42). Therefore, our results may also be useful if the deadly, closely related fungal pathogen Batrachochytrium salamandrivorans (43) reaches this salamander biodiversity hot spot (44).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…dendrobatidis bacteria likely have general antimicrobial properties (52) and may provide a general defensive benefit against pathogens to the host (9,13,23,42). Therefore, our results may also be useful if the deadly, closely related fungal pathogen Batrachochytrium salamandrivorans (43) reaches this salamander biodiversity hot spot (44).…”
Section: Discussionmentioning
confidence: 98%
“…Lower disease risk in vertebrates has been associated with different characteristics of the microbiome, such as high bacterial species richness (6)(7)(8), specific microbial community assemblages (2,7,9,10), and the presence of microbes that produce metabolites that inhibit growth of pathogens (1,11,12). For amphibians, inter-and intraspecies-specific variations in the skin microbiome (13)(14)(15) may contribute to variation in responses to infection by the deadly fungal pathogen Batrachochytrium dendrobatidis (16,17).…”
mentioning
confidence: 99%
“…() reported the numerical dominance of both Actinomycetales and Sphingomonadales on the skin of toads and their possible antifungal role. The Pseudomonadales, particularly those of the genus Pseudomonas , contain several species known to provide protection against pathogenic bacteria and fungi (Chang, Huang, Lin, Huang, & Liao, ; Federici et al., ). The Enterobacteriales were dominant in this study, and while this order has been reported from the guts of frogs (Chang et al., ), we found only two reports from amphibian (toad) skin studies (Hughey et al., ; Bataille et al.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research pertaining to frog skin microbiota has focused on the complexities of the epidemic of chytrid fungus (Rollins-Smith et al, 2011;Jani & Briggs, 2014;Holden et al, 2015;Berger et al, 2016;Bates et al, 2018) and other frog skin diseases (Federici et al, 2015;Knutie et al, 2017), including suggestions of using probiotics on frog populations (Harris et al, 2009;Loudon et al, 2014;Küng et al, 2014) even at a landscape scale (Muletz, Myers, Domangue, Herrick, & Harris, 2012). These efforts have yielded inconclusive results, including problems associated with the resilience of the skin microbiota inhibiting the uptake of probiotics (Küng et al, 2014).…”
Section: Biologic Factors Include Transitions In Life Stagesmentioning
confidence: 99%
“…Within amphibians, members of these families are commonly described as part of the skin microbiota (Jiménez & Sommer, ). However, Batrachochytrium dendrobatidis infection can induce a positive response in the abundance of Comamonadaceae , Flavobacteriaceae and Moraxellaceae (Federici et al., ; Jani & Briggs, ; Walke et al., ), and studies recording the effects of captivity on the skin of amphibians have recorded positive responses in members of these families as well (Becker et al. ).…”
Section: Discussionmentioning
confidence: 99%